The effects of various growth factors on the proliferation of human nasal septum chondrocytes and reconstruction of human cartilage via tissue engineering technology - Chua, Kien Hui; Saim, Aminuddin; Idrus, Ruszymah (Penerbit Universiti Sains Malaysia, 2004)
Tissue loss and organ failure are one of the costly health care management in all over the world. One of the recent strategies for the treatment of organ failure and damaged tissues is via tissue engineering technology. The primary goal of all approaches in tissue engineering is to repair and restore tissue functions through the delivery of living elements which become integrated into the patient (Langer and Vacanti, 1993).